Well-child care delivery in the community in China: Related factors and quality analysis of services. - Pan Mao; Hui Feng; Shuang Xu; Jianghong Liu; Huayan Li; Yaying Zhang; Yiyan Ye (PLoS ONE, 2018)
Well-child health care services are essential for maintaining optimum child health and development. This study's aim was to evaluate the quality of such services and identify factors affecting service quality from the perspective of well-child health care providers located in China's Hunan Province. To achieve this, a qualitative descriptive method was employed, with 22 well-child health care providers being recruited, using purposive sampling, from among the provinces' government community health centers. The participants completed individual semi-structured interviews lasting approximately 25-30 minutes that were designed to obtain their views on well-child health care administration in the province. Then, the interview transcripts were analyzed thematically. The main finding was that participants felt that the delivery of well-child health care services in Hunan Province is insufficient. Factors they mentioned as negatively affecting the delivery of such services included the region's fragmented primary health care system, inadequate attention to this issue from parents and community health care center managers, and a lack of specialized well-child care knowledge. Thus, currently, well-child health care is not being successfully implemented in Hunan Province; consequently, in order to successfully implement well-child health care in this region, community health care centers should invest more resources and funding, particularly into education programs for well-child health care providers.